The preparation and the performance of a Humanitarian Aid Force of the Brazilian Army - Gomes, Thiago da Rocha Passos (2024)
The objective of this work was to verify how the Brazilian Army prepares a Humanitarian Aid Force and how it acts in cases where it supports civil defense in situations of humanitarian disaster. In this context, this research conducted a case study on the sixth humanitarian aid exercise, carried out in the year 2022 by the 14th Motorized Infantry Brigade, in the city of São Francisco do Sul, Santa Catarina. For this purpose, data were collected through bibliographic review and through the participant observation of one of the authors of the article, in addition to an interview with an army officer who participated in the organization of the exercise. As a result, the needs for the effective performance of a Humanitarian Aid Force in the national territory were verified.